Stehende Flüsse - Ochs, Markus; Gieringer, Johannes; Leibel, Philipp (Austria; Germany, 2011)
The South-East-Anatolien project is the largest developing project of Turkey. Since the 80‘s the Turkish state builds dams in the southeast of Turkey and decides over the heads of the people. Families are resettled by force and fields are flooded. Missing perspectives and a lack of jobs force humans to migrate into the larger cities. One of the oldest cultivated landscape is going to be depopulated. The documentary shows the life of affected humans, their fates, desires and longings and gives a voice to those, whose opinions don´t count.
Verzio Film Festival Submission
Keywords: Documentary films